The Effect Of Reporting Financial Quality and Practices Accounting Ethical: Deposit Money Banks In Nigeria Perspective - Iyere Samuel Iheonkhan; Sulaiman Taiwo Hassan (International Journal of Management Research and Economics, 2024)
This study looks into how Nigerian deposit money banks behave with creative accounting. Five deposit money institutions in Nigeria were included in the ten-year sample, which ran from 2007 to 2016. The study's multiple regression analysis showed that the performance of banks is not much impacted by non-performing loans. Additionally, it was discovered that while gross earnings significantly improved the performance of Nigerian deposit money institutions, total accrual had no discernible impact on that performance. While it would be absurd to believe that banks' creative accounting procedures have no good impact at all, it is possible to reduce their negative consequences to a minimum by implementing the International Financial Reporting Standard (a new standard), which places greater emphasis on ethical factors and reduces bank managers' latitude in selecting various accounting techniques. Financial statement fraud would be further decreased and of higher quality as a result.